2019
DOI: 10.3390/f10070544
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Labile and Recalcitrant Pools of Carbon and Nitrogen in Forested and Agricultural Soils: A Study under Tropical Conditions

Abstract: Soil organic carbon and nitrogen can be divided into labile and recalcitrant pools according to the time it takes to be cycled. The way in which carbon and nitrogen pools are cycled and distributed between labile and recalcitrant pools can directly relate to soil quality. This paper tested the hypothesis that labile and recalcitrant pools of carbon and nitrogen vary between agricultural soils with different species and fertilization management systems (nitrogen, phosphorus, and potassium need) under tropical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…This may be owing to the gradual decomposition of organic amendment in the early oat growth period providing enough carbon source, while the oat grows rapidly at the heading stage, and the enhancement of photosynthesis improves the carbon fixation capacity of oat [38]. In this experiment, soil TNP and TPP basically remained stable throughout the growth period, which was not consistent with former studies that confirmed that the application of organic fertilizers can increase soil carbon and nitrogen pools [39]. It may be because nitrogen is usually present in organic matter in the form of organic nitrogen, which makes the changes in soil carbon and nitrogen more synchronized [40].…”
Section: Redundancy Analysiscontrasting
confidence: 87%
“…This may be owing to the gradual decomposition of organic amendment in the early oat growth period providing enough carbon source, while the oat grows rapidly at the heading stage, and the enhancement of photosynthesis improves the carbon fixation capacity of oat [38]. In this experiment, soil TNP and TPP basically remained stable throughout the growth period, which was not consistent with former studies that confirmed that the application of organic fertilizers can increase soil carbon and nitrogen pools [39]. It may be because nitrogen is usually present in organic matter in the form of organic nitrogen, which makes the changes in soil carbon and nitrogen more synchronized [40].…”
Section: Redundancy Analysiscontrasting
confidence: 87%
“…After accumulating residues in the soil, microorganisms are responsible for decomposition with about 80% of C lost with CO 2 emissions, and 20% of C incorporated into the soil. In regions where there is a predominance of high temperatures associated with water inputs, the oxidation of organic matter is faster due to the increment of biological activities (i.e., beta-glucosidase enzymes) [2][3][4][5][6][7][8][9][10][11]. The semi-arid region presents a long dry period during March and November, and a rainy period during December and February; both periods present high temperatures.…”
Section: Carbon and Soil Porositymentioning
confidence: 99%
“…Buso et al [6] showed that sorghum has a high capacity to produce high-quality forage for animal feed, mainly in periods of low production of cultivated or native systems with cactus (Opuntia stricta; [7]), crotalaria (Crotalaria ochoroleuca; [8]), soybean (Glycine max; [9]), cowpea (Vigna unguiculate [10]), and different grass cultivars (e.g., Brachiaria sp. [11]). Mattos et al [12] showed that B. brizantha cv.…”
Section: Introductionmentioning
confidence: 99%
“…Based on classical extraction procedures and the solubility in water as a function of pH, the SOC is conceptually made up of humic acid (HA), fulvic acid (FA), humin, and glucose equivalent total non-humic carbon (NH) pools [1,16,17]. While the functionality of the HA, FA, and humin pools is based on its aliphatic and aromatic chemical composition, the NH pool, in contrast, is composed mainly of labile polysaccharides and protein-based compounds [1,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, these C compounds originate during and/or after plant and animal residue decomposition and subsequent polymerization of metabolites into complex and heterogenic mixture of SOC pools with distinct functional groups, chemical composition, and physico-chemical properties [1,8]. It is reported that the HA, FA, and humin pools are themselves not biologically passive but rather they accumulate in soil due to the various degrees of complexations with polyvalent cations and clays with limited microbial access to carry-out ecological functions [17,21].…”
Section: Introductionmentioning
confidence: 99%